Literature Review on Trends of Comprehension Instruction for Elementary School Students - Parlindungan, Firman; Prasetya, Willy (JURNAL PENDIDIKAN DAN PENGEMBANGAN MANUSIA, 2022)
Abstract: The objective of this article is to construct evidence-based arguments on what comprehension is and what are various instructional approaches to improve comprehension post the National Reading Panel’s (NRP) report (2000). The NRP (2000) reported seven text comprehension instructions that have scientific evidences in improving reading comprehension. Those instructions are: (1) comprehension monitoring, (2) cooperative learning, (3) graphic and semantic organizers, (4) question answering, (5) question generation, (6) summarization, and (7) multiple strategies. It has been more that 20 years since the NRP reviewed empirical evidences of those text comprehension instructions. What have we learnt since then? Having reviewed 29 studies on comprehension instruction published in the past twenty years, we found top three comprehension instructions that are used in elementary classroom. They are: (1) differentiated/individualized reading instruction, (2) vocabulary-based reading instruction, and (3) transactional approach. These findings informed us that further research on elementary reading comprehension instruction needed. Also, the NRP categorization of comprehension instruction (2000) needs modification.